High incidence of aseptic hip necrosis in Hodgkin lymphoma patients treated with escalated BEACOPP receiving methylprednisolone. Issue 5 (2nd May 2018) - Basic‐Kinda, Sandra; Karlak, Ivan; Durakovic, Nadira; Lubina, Zvonimir I.; Livaja Radman, Ivo; Dotlic, Snježana; Peric, Zinaida; Hude, Ida; Aurer, Igor
Abstract: Background: Escalated BEACOPP (eBEACOPP) is an effective but fairly toxic regimen for the treatment of Hodgkin lymphoma (HL). Avascular necrosis (AVN) of femoral head was previously reported to increase in patients treated with eBEACOPP, but so far, no systematic analysis of its frequency has been published. Aims: To analyse the frequency and identify possible risk factors for AVN development in patients treated with eBEACOPP. Methods: We identified 26 patients treated with eBEACOPP for newly diagnosed high‐risk advanced‐stage HL, 25 of whom were alive at the time of study. All patients were invited to participate in a cross‐sectional study; 17 patients responded and were evaluated by magnetic resonance imaging and orthopaedic examination. Results: Six patients (35.3%) were diagnosed with AVN after receiving eBEACOPP treatment. AVN was not correlated with age, gender, number of received eBEACOPP cycles, irradiation therapy or cumulative dose of steroids administered. There were significantly more cases of AVN in patients receiving methylprednisolone than prednisone ( P = 0.01). Conclusion: The use of methylprednisolone was shown to be a risk factor for the development of AVN in patients treated with eBEACOPP and should not be the corticosteroid of choice in the treatment of patients with HL.